The Integration of Total Quality Management in Islamic Education Supervision: A Systematic Literature Review within the Framework of Society 5.0 - Samsudin Samsudin (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The transformation of education in the Society 5.0 era requires Islamic educational institutions to not only be adaptive to technological advancements but also capable of developing sustainable quality assurance systems. Although Total Quality Management (TQM) has been widely adopted in educational management, its integration into the practice of Islamic education supervision has not yet been formulated comprehensively. This study aims to analyze the integration of TQM into Islamic education supervision through the lens of Society 5.0 and to develop a relevant integrative conceptual model addressing the challenges of digital transformation.This research employs a library research method with a systematic literature review approach. Data sources were obtained from academic books and scientific articles relevant to TQM, educational supervision, Islamic education, and Society 5.0. The data were analyzed through processes of reduction, categorization, and conceptual synthesis to identify patterns, trends, and gaps in previous studies. The results indicate that: (1) the implementation of TQM in Islamic education is still dominated by general managerial aspects and has not been systematically integrated into learning supervision; (2) Islamic education supervision is undergoing a transformation toward a collaborative, reflective, and data-driven model aligned with the principles of continuous improvement; and (3) there is a need for an integrative model that combines the TQM paradigm, reflective supervision, and human-centered digital transformation within the framework of Society 5.0. This study contributes to the development of a conceptual model for quality management in Islamic education that is adaptive, systemic, and oriented toward the continuous improvement of learning quality.